Effect of Acupuncture Therapy and Ear Apex Bloodletting on Blood Pressure in Hypertension Patients at Posyandu Sumberejo Village, Bonang District, Demak Regency - Niha, Nihayatut Taqiyyah; Presetya, Hanung; Yatmihatun, Sri; Zulaika, Chusnul (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Hypertension is a condition where the measurement results of systolic blood pressure are ≥140 mmHg and diastolic blood pressure ≥90 mmHg. The prevalence of hypertension in Demak Regency is 76.7%, the second highest in Central Java. Acupuncture therapy and ear apex bloodletting are nonpharmacological treatments that can be used to treat hypertension. The purpose of this study was to analyze the effect of acupuncture therapy and ear apex bloodletting on hypertension cases at Posyandu Lansia Desa Sumberejo, Bonang District, Demak Regency. This study used a quantitative method with a quasi-experimental design with a two-group pretest-posttest design. This study used 30 samples that met the inclusion and exclusion criteria, which were divided into 15 people per group. The first group of acupuncture therapy, the second group of acupuncture therapy, and ear apex bloodletting. Mann-Whitney test results showed sig. <0050 in the acupuncture and bloodletting therapy group on systolic blood pressure. Wilcoxon test results show both groups get sig results. <0.05, which indicates that there is an effect on blood pressure from group I and II treatments. In conclusion, acupuncture and ear apex bloodletting are more effective in reducing systolic blood pressure